Mental health in children with and without ADHD: the role of physical activity and parental nativity - David Adzrago; Saanie Sulley; Faustine Williams (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Physical activity (PA) can improve mental health, including anxiety/depression, in individuals with attention-deficit/hyperactivity disorder (ADHD) with minimal side effects, unlike pharmacotherapy that can result in significant side effects. However, the influence of PA on mental health among children with ADHD is understudied. Also, immigrants tend to have better mental health, but the influence of parental nativity on children’s mental health is unknown. We examined the relationship between PA, parental nativity, and current anxiety/depression among U.S. children with and without ADHD. We also analyzed whether ADHD diagnosis status moderates the relationship between anxiety/depression and PA or parental nativity. Methods We used national annual cross-sectional data from the 2016 to 2021 National Survey of Children’s Health to conduct weighted multivariable logistic regression and moderation analyses, with current anxiety/depression status as the outcome variable. The sampling involves selecting households with children and rostering children in the household from each state and the District of Columbia. A parent or caregiver of the selected child completes the surveys. We restricted the analysis to children aged 6–17 years (N = 140,977). Results The prevalence of current anxiety/depression was higher in children with ADHD diagnosis (37.34%) than those without ADHD diagnosis (7.42%). Children with ADHD (versus no ADHD) had higher odds of anxiety/depression. Engaging in PA (versus no PA) and having immigrant parents (versus non-immigrant parents) were associated with lower anxiety/depression odds. ADHD diagnosis status significantly moderated the association between anxiety/depression and PA or parental nativity. However, the three-way interaction between ADHD status, parental nativity, and physical activity was not statistically significant. Stratified by ADHD diagnosis status, those who engaged in PA (versus did not) for 1 to 3 days, 4 to 6 days, and daily were less often diagnosed with anxiety/depression disorder among those with or without ADHD, especially children without ADHD. The odds were also lower for children with or without ADHD whose parents were immigrants than children with non-immigrant parents, particularly children without ADHD who had immigrant parents. Parental nativity did not significantly moderate the association between PA and anxiety/depression among children with and without ADHD. Conclusions Physical activity was associated with lower risks of diagnosed with anxiety/depression disorder among children, especially children without ADHD and those with immigrant parents. Considering parental nativity and incorporating personalized PA in ADHD and anxiety/depression management can improve mental illness and ADHD symptoms among children.